La configuration des territoires des peuples en isolement « volontaire » - Kelly Johanna Escobar Jiménez (Revue d'anthropologie des connaissances)
Our goal is to interrogate the uncertainty prior to the management of Amazonian territories and to show how each program relaunch exploitation of natural resources there are controversies that require re-examination of ways of knowing, ways of entering into relationships and ways of managing territories Amazon and its human populations and non-human. We do so through those people in “voluntary isolation” We’ll see how the debates linked to the “isolated peoples” does not only concern the management of territory and population, but also the forms of knowledge production entities silent. How, where, what, how to contact without reducing our Western or virus without dying with their spears, how to talk about entities that temporarily can not, definitely do not know, or at times unwilling to do so, here are some questions that emerge in the middle of the race of internal colonization of the Amazon. We tried to understand this silent isolation from the analysis of two cases, the case of the Serviço de Proteção aos Índios (SPI, 1910-1967) in Brazil and the case of Seminario Regional Pueblos indígenas en aislamiento voluntario y contacto inicial en la Amazonía y el Gran Chaco (Santa Cruz de la Sierra, Bolivia, 2006). We found some controversies and testify to the complexity of the issue and force us to reconsider the importance of the nature of the population to manage at the time to configuration of protected areas.